(untitled) (Third Sector Social Economic Review, 2026)
The curriculum of higher education programs and departments is affected and updated due to reasons such as national and international developments, published standards, changes in national legislation, opinions of professional members, university-industry collaborations, opinions of stakeholders and innovations in technology, etc. The purpose of this study is to identify and compare the current status of the curricula of associate and undergraduate departments and programs offering direct accounting education at state and foundation universities in Turkey using content analysis, a qualitative research method. As part of the study, associate degree programs and departments in Accounting and Tax Applications and undergraduate programs in Accounting and Financial Management were identified using YÖKATLAS 2024 data. Curriculum data was then collected and classified in Excel by accessing the course catalogs of these universities’ websites. The study found that general accounting, cost accounting, corporate accounting, packaged programs, and accounting auditing were the most common compulsory courses at both the associate and undergraduate levels of state and foundation universities. As expected, the number and load of courses at the undergraduate level are twice as long as those at the associate degree level, paralleling the duration of study. The curricula of state and foundation universities are similar in content.